ØªØ£Ø«ÙŠØ± ÙˆØ³ÙŠÙ„Ø© Ø§Ù„Ù‚ØµØ© Ø§Ù„Ù…Ù‚Ø·Ø¹ÙŠØ© (Strip Story) ÙÙŠ ØªØ±Ù‚ÙŠØ© Ø¥ØªÙ‚Ø§Ù† Ù…ÙØ±Ø¯Ø§Øª Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© - Wirdiatun Wizri wirdiatun; Ruwaida Hudatullah; Siti Rauhillah (Lughatu Ad-dhat, 2022)
Among the many problems learning Arabic are the media, methods of learning Arabic, and enthusiasm for learning Arabic. In this university research, the researcher focused on the media, specifically through the use of the Strip story method, considering this method is suitable for learning vocabulary. The questions "Does the application of the "Strip Story" method affect the upgrading of Arabic vocabulary proficiency? The objectives of the research are to find out the effect of the application of the "Strip Story" method in improving Arabic vocabulary. The research hypothesis exists that the effect of the "Strip Story" method To improve the proficiency of Arabic vocabulary. This research uses the quantitative method and uses the type of experimental research. The population research and the samples research were students of class VII-Q experimental class and class VII-h class control. Undergraduate research is the use of an objective test in the form of a multiple choice test. The mean score for the pre-test for the control group was 56.25, while the mean for the post-test score for the control group was 55.16, and thus it can be concluded that we are as a decrease in learning outcomes in the control group using the lecture method.The average score of the pre-test for the experimental group is 60.00, and the average score for the post-test for the experimental group is 73.75, and it can be concluded that as an increase in the results of students learning the Arabic language using the strip story method